Possessive Relational Process Clauses in Scientific Text: Implication on ESP Teaching - Mulyati Khorina (Jurnal Bahasa Inggris Terapan, 2018)
This paper focuses of this paper aimsis possessive relational process clauses which is a type of relational process clauses in which relational processes work. Threepoints concerning possessive relational process clauses are discussed in this paper. First, the relational process type which is dominant possessed by possessive relational process clauses. Second, the lexical verbs which realize the dominant type of relational process. The last, the roles played by possessive relational process clauses. The data for this study were taken from Electrical Circuit Theory and Technology, Fundamentals of Electronics Circuits, Electronics Devices, Flow Version, and A Textbook of Electrical Technology, all of which are used as references by  Electronics Engineering students of PoliteknikNegeri Bandung. To analyse the data, Systemic Functional Linguistics (SFL) was employed. The results showed that possessive relational process clauses in scientific texts operate solely on attributive relational process. The attributive relational process is realized by lexical verbs have, consist, include, make which represent the possessive relational process clauses as Classification, Composition and Feature.